IMPACTOS DO USO DE CHUPETA E MAMADEIRAS NA DENTIÇÃO E NO DESENVOLVIMENTO CRANIOFACIAL (REMUNOM, 2024)
The objective of this study is to analyze the impacts of prolonged use of pacifiers and bottles on the development of the deciduous and craniofacial dentition of children, highlighting the role of the dental surgeon in the prevention and treatment of these changes. The methodology used was an integrative literature review, covering studies published between 2014 and 2024, selected in the SCIELO, LILACS, PubMed, Science Direct, and Virtual Health Library databases. The results indicate that the prolonged use of pacifiers and bottles is associated with malocclusions, such as anterior open bite and posterior cross bite. In addition, there is a significant correlation between the use of these devices and the occurrence of respiratory, speech and irregular bone development disorders. Children breastfed for more than six months showed a lower prevalence of pacifier use, while those who use pacifier for more than one year are more likely to develop malocclusions. In conclusion, the study highlights the importance of preventive and educational interventions from the first years of life. Educational programs aimed at parents and caregivers can play a crucial role in reducing the prevalence of deleterious oral habits and, consequently, in promoting children's oral and craniofacial health. It is essential that dental professionals are attentive and act proactively in the guidance and treatment of children to prevent and mitigate the negative impacts of these habits.